Assessment of factors affecting the volume of agricultural production in the regions of Russia (Agroindustria, Sociedad y Ambiente, 2022)
The study was based on the development of production functions that characterize the activities of agricultural enterprises in the regions of Russia. Official statistical information on 65 regions of Russia for 2017 and 2018 was used. The conducted research made it possible to identify factors (investments in fixed assets, wages of employees and arable land area) that affect the volume of production in the agricultural sector in the regions of Russia and suggest using three -factor production functions of high quality to describe this influence. It is proved that the economy of the country's regions has not reached saturation with agricultural products and there are significant reserves for further development of this sector. The developed production functions are effective management tools that allow assessing the level of use of financial and labor resources. The acquired new knowledge and tools for assessing the activities of agriculture in the Russian regions are of scientific and practical importance. They can be used in research of the agricultural sector of the economy, monitoring of production volumes, in determining the needs for resources necessary for the development of agriculture, substantiating plans and programs for its development.
Keywords: Production function; agriculture; investments in fixed assets; wages; arable land area; regions of Russia